Aggregate Distribution and the Associated Carbon in Norfolk Soils under Long-term Conservation Tillage and Short-term Cover Cropping. Issue 8 (28th April 2021) - Parajuli, Binaya; Luo, Min; Ye, Rongzhong; Ducey, Thomas F.; Park, Dara; Smith, Matthew; Sigua, Gilbert
ABSTRACT: Conservation agriculture practices have been widely implemented to improve soils and their sustainability. Here, we investigated the impacts of long-term conservation tillage (CS) on soil aggregates and their associated carbon (C) in a typical sandy Ultisols. The short-term effect of cover cropping was also investigated. Soils (0–5 and 5–15 cm) were collected from fields under 40-years CS and conventional tillage (CV), in which cover crop and fallow treatments were embedded as a split-plot design for four years. Soils were tested for bulk density, pH, mean weight diameter, dry aggregate distribution, and C contents. The CS only resulted in higher total C (TC) concentrations (13.56 ± 1.14 g kg −1 ) than CV (10.06 ± 0.53 g kg −1 ) at 0–5 cm. Similar depth impacts were observed in various aggregate size fractions (2000–250 µm, macroaggregates; 250–53 µm, microaggregates; 0–53 µm, clay-silt fraction). Soils were dominated by macroaggregates (>50%) at both depths with associated C concentrations following the order of clay-silt fraction > microaggregates > macroaggregates. Nonetheless, after accounting for soil bulk density long-term CS did not result in higher TC stocks than CV at both depths. Cover crops demonstrated no effect on C stocks at both depths. Poor soil structure and low clay contents of the tested soils may partially explain these neutral impacts, while relatively lower residue returns of cover crops to cash crops may also confound the positive management outcomes. Novel management practices to increase soil organic C in the bulk soils by increasing organic inputs and the soils' capacity to preserve the inputs are needed.